Clinical outcomes with ustekinumab as rescue treatment in therapy‐refractory or therapy‐intolerant ulcerative colitis. Issue 1 (1st February 2020) - Ochsenkühn, Thomas; Tillack, Cornelia; Szokodi, Daniel; Janelidze, Shorena; Schnitzler, Fabian
Abstract : Background: Recently, ustekinumab a monoclonal antibody targeting interleukin‐12 and −23 and successfully used in Crohn's disease also has been shown to be effective in induction and maintaining remission in patients with moderate to severe ulcerative colitis in a large phase 3 trial. However, no observational data on the use of ustekinumab in ulcerative colitis in daily clinical practice is available. Aim: The purpose of this study was to assess the clinical outcomes achieved with ustekinumab as rescue treatment in therapy‐refractory or ‐intolerant ulcerative colitis in a real‐life setting. Methods: A retrospective data analysis was performed in 19 ulcerative colitis patients who were intolerant or refractory to all of the following drugs: steroids, purine‐analogues, tumour necrosis factor antibodies and vedolizumab. To all patients ustekinumab was provided as a rescue treatment (intravenous induction with 6 mg/kg, followed by week subcutaneous injection once every eight weeks of 90 mg). The primary outcome was achievement of clinical remission at one year, defined as score of ≤ 3 points in the Lichtiger score (colitis activity index). Patients were evaluated regularly and a colonoscopy was performed before the start and at the end of the observation. Ethical approval was provided by Ethikkommission Ärztekammer Hamburg (PV 5539). Results: In five patients, therapy was stopped due to refractory disease or side effects. In all remaining 14 patients the median colitis activity index dropped from 8.5 points (range 1–12) at start to 2.0 points at one year (range 0–5.5) and Mayo endoscopy scores fell from a median of two points (range 1–3, mean of 2.3) at start to a median of one point (range 1–3, mean of 1.4) at one year. Including the five drop‐outs, clinical remission was achieved in 53% of the 19 patients at one year. Conclusions: In accordance with the UNIFI (A Study to Evaluate the Safety and Efficacy of Ustekinumab Induction and Maintenance Therapy in Participants With Moderately to Severely Active Ulcerative Colitis) trial our real‐life data support ustekinumab as an effective and safe treatment option in therapy refractory moderate to severe ulcerative colitis with a history of biological therapies.